Issues in Effective Teaching Learning in Tourism Education - Thomas, Toney K (Atna Journal of Tourism Studies, 2007)
Three percentage of th total research in tourism is taking place in education (David Airey, 2006) . Quality education in tourism is a platform for sustainable industry development. The study reviews and evaluates the effectiveness of teaching and learning in tourism and its effectivenss in putting prctice thse skill in the industry and to propose an alternative strategy to reduce the gap in tourism eduication and the end users . Discussion of this paper has been focussed on the practices in tourism education institutions and critical and analytical thinking ability which links candidate to the institutte and to the field of operation in order to increase the capacity in tourism education. In other way taking the erning outcomes in the form of knowledge and skill to put practice effectively in the field of tourism indsutry. For a successful pratice it needs a practical focus from the education institutions.